THE EFFECT OF ACROSTIC LEARNING METHODS ON THE ABILITY TO WRITE POETRY IN JUNIOR HIGH SCHOOL STUDENTS - Gustianty, Fahra Elvy; Arianto, Arianto; Rangkuti, Sukma Adelina (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2022)
This study aims to determine the effect of the acrostic learning method on the ability to write poetry in class VIII SMP Al-Wasliyah 24 Medan in the 2017-2018 academic year. Learning to write provides many benefits, including developing creativity, instilling courage and confidence, and helping students express ideas, thoughts, experiences, feelings and ways of looking at life. Seeing the many benefits that students will get in learning to write, writing activities should be an activity that students are interested in. However, the reality in some schools shows that writing is still a difficult activity for students. Students' difficulties are natural because writing poetry requires a process and is strongly influenced by habits, students' vocabulary mastery and choice of diction. The ability to write poetry for class VIII SMP Al-Wasliyah 24 Medan before using the acrostic learning method is very poor because it can be seen from the results of the study that students' scores are still much below the KKM with an average value of 36.18. Therefore, the researchers tried to solve these problems by using the acrostic learning method. This research is a type of quantitative research. in this study, researchers used experimental research. Experimental research is quasi-experimental or not. Therefore, the population in this study was set at class VIII-1 students, which amounted to 30 students and became the total sample. To obtain data in the study of poetry writing skills, a test of Indonesian language learning outcomes was used for students with poetry writing material. The design in this experimental study uses a Pre-test Post-test Design which provides an initial ability test and then after doing the treatment students are given a learning outcome test to see the effect of learning outcomes after using the acrostic method. From this research, it shows that the score of the results of writing poetry has increased and is included in the good category (86.54). From the calculation of the correlation coefficient, the price (727.83 > 0.361) means that there is an influence of the Acrostic Learning Method on the Ability to Write Poetry in Grade VIII Students of SMP Al-Wasliyah 24 Medan in the 2017-2018 Academic Year.